To the problem of teacher training in the modern dimension of art education - Komarovska, Oksana; Myropolska, Natalia (Professional Art Education, 2022)
The purpose of the article is to analyze and define the conceptual vectors of the development of modern art education and the specifics of training a competent teacher of art disciplines in this field.Methods and methodology. The solution of the outlined scientific problem involved the use of a systemic approach, which made it possible to determine the conceptual dominants of art education and characterize them. An objective substantive analysis of the views of scientists in the fields of philosophy, cultural studies, pedagogy, and music pedagogy regarding the aesthetic component of personality formation contributed to a comprehensive consideration of the problem of art education and professional competence training of the future teacher of art disciplines. The application of the activity approach made it possible to develop certain recommendations for the creative use of educational material in the course of the discipline "Artistic culture" in the tenth grade of general secondary education institutions.The scientific novelty of the article lies in the definition and characteristics of the conceptual vectors of the development of modern art education, recommendations are provided for the creative use of the content of the subject "Artistic culture" (10th grade) in the formation of the artistic and aesthetic competence of the individual.Results. The problems of modern art education are revealed, among which, on the one hand, trends in the aesthetic arrangement of life, and, on the other hand, uncontrollability and manipulation of this process. The conceptual vectors of building an art education strategy are singled out and the possibilities of their implementation are demonstrated on the example of teaching the subject "Artistic culture" (10th grade). Emphasis is placed on teacher training. Art education is defined as a universal aesthetic-educational and personal-developmental component of education. Attention is paid to essential indicators of the professional competence of the future teacher of art disciplines. The peculiarities of their possession of the pedagogical tools of cultural phenomena are revealed both at the level of aesthetic dominants of the historical context in which they were created, and at the level of modern sound. It has been found that operating the mechanisms of such a dialogue makes it possible to liberate certain boundaries of artistic knowledge, which is necessary now, awakening the creativity of the individual - both the teacher and the student, which is a perspective of art pedagogy research.
Keywords: school education through art; artistic culture; aesthetic education; image model of the world; conceptual vectors